2022
DOI: 10.1101/2022.09.29.510004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity of diffusion-tensor and correlated diffusion imaging to white-matter microstructural abnormalities: application in COVID-19

Abstract: There has been growing attention on the effect of COVID-19 on white-matter microstructure, especially among those that self-isolated after being infected. There is also immense scientific interest and potential clinical utility to evaluate the sensitivity of single-shell diffusion MRI methods for detecting such effects. In this work, the sensitivities of three single-shell-compatible diffusion MRI modeling methods are compared for detecting the effect of COVID-19, including diffusion-tensor imaging, diffusion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In the first study, low diffusion restriction in frontal circuits and high diffusion restriction in cerebellum were found in patients with COVID-19 compared to controls 32 . In the second study, Tellet et al demonstrated reduced cerebral blood flow (CBF) in the thalamus, basal ganglia, and orbitofrontal cortex in COVID-19 patients compared to controls 33 . With regard to possible fluid biomarkers, in patients with long COVID there is an activation of the inflammasome mediated by SARS-Cov-2 and a subsequent dysregulated inflammatory response, with consequent persistent elevation of pro-inflammatory cytokines such as IL-1, IL-6 and TNF-alpha 26,[34][35][36] .…”
Section: Cognitive Symptomsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the first study, low diffusion restriction in frontal circuits and high diffusion restriction in cerebellum were found in patients with COVID-19 compared to controls 32 . In the second study, Tellet et al demonstrated reduced cerebral blood flow (CBF) in the thalamus, basal ganglia, and orbitofrontal cortex in COVID-19 patients compared to controls 33 . With regard to possible fluid biomarkers, in patients with long COVID there is an activation of the inflammasome mediated by SARS-Cov-2 and a subsequent dysregulated inflammatory response, with consequent persistent elevation of pro-inflammatory cytokines such as IL-1, IL-6 and TNF-alpha 26,[34][35][36] .…”
Section: Cognitive Symptomsmentioning
confidence: 98%
“…Douaud et al described, using brain MRI, gray matter atrophy in the orbitofrontal cortex and parahippocampal gyrus in 401 post-COVID-19 patients compared with pre-COVID-19 examination of the same patients 28 . Other promising magnetic resonance imaging (MRI) techniques in the study of these patients are diffusion tensor imaging (DTI) and arterial spin labeling, which were even used in patients with long COVID by Kim et al and Teller et al, respectively 32 , 33 . In the first study, low diffusion restriction in frontal circuits and high diffusion restriction in cerebellum were found in patients with COVID-19 compared to controls 32 .…”
Section: Cognitive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation